Teaching behavior profile in clinical student-teacher interactions at the University of the Philippines College of Dentistry - Salinda, Maria Cecilia G. (2004)
This study aimed to categorize teaching behaviors that occurred and identify teaching-learning climates that prevailed during student-teacher interactions at the Oral Medicine, Operative Dentistry, and Prosthodontics Sections of the Department of Clinical Dentistry, University of the Philippines College of Dentistry. Using qualitative research methods, twenty-one clinical faculty members and forty-seven clinicians were observed in sixty-three student-teacher interactions. Teaching behaviors were categorized by identifying ways by which clinical faculty members taught critical thinking (CT) skills, determined if these teaching behaviors fostered CT, determined what factors fostered CT. The frequency of emergent teaching behaviors categories and prevailing teaching-learning climate were tabulated. The teaching behaviors were categorized as "Authoritative/Teacher-Dominated," "Teaching Critical Thinking Skills," Coaching/Mentoring," and "Evaluating Student Performance." The most predominant teaching behavior observed was "Authoritative/Teacher-Dominated" and characterized by allowing minimal student participation, asking "what" questions or engaging in didactic teaching. "Teaching Critical Thinking Skills" was the second predominant teaching behavior observed wherein teachers allowed students to participate, asked "How" and "Why" questions, or shared their thought process. "Coaching/Mentoring" was characterized by teachers cueing, monitoring or coaching students while they performed dental procedures or during case coaching students while they performed dental procedures or during case discussion. When teachers primarily checked dental procedures, patients' charts or treatment plans, these were categorized as "Evaluating Student Performance." The last two teaching behaviors were least observed. The majority of teaching behaviors in observed student-teacher interactions were insufficient in fostering critical thinking skills among clinicians. While a supportive-collegial teaching-learning climate prevailed during observed student-teacher interactions.
Major project (Master in Health Professions Education)--University of the Philippines Manila
Keywords: Teacher-student relationships